2018
DOI: 10.1186/s12938-018-0438-z
|View full text |Cite
|
Sign up to set email alerts
|

Computational study of the effects of arterial bifurcation on the temperature distribution during cryosurgery

Abstract: BackgroundThermally significant blood flows into locally cooled diseased tissues and warm them during cryosurgery so that the iceball is often hard to cover the whole diseased volume. This paper is aimed at investigating the effects of large arterial bifurcation on the temperature distribution during cryosurgery through simulation method.MethodsA parametric geometry model is introduced to construct a close-to-real arterial bifurcation. The three-dimensional transient conjugate heat transfer between bifurcated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…The density of blood is set to 1050 kg/m 3 , and the viscosity of blood is 0.0035 Pa•s. The time-independent blood flow field is solved though using the SIMPLE algorithm, and the stable temperature field through the second-order upwind algorithm is obtained [17]. The mesh quality significantly affects the simulation results, while the excessively small mesh size would lead to high computing resources needed.…”
Section: Fluid Dynamics Simulation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The density of blood is set to 1050 kg/m 3 , and the viscosity of blood is 0.0035 Pa•s. The time-independent blood flow field is solved though using the SIMPLE algorithm, and the stable temperature field through the second-order upwind algorithm is obtained [17]. The mesh quality significantly affects the simulation results, while the excessively small mesh size would lead to high computing resources needed.…”
Section: Fluid Dynamics Simulation Methodsmentioning
confidence: 99%
“…The initial blood temperature assumes as 37°C. The thermal conductivity of blood is set to 0.55 W/m•K [17]. Fig.…”
Section: Fluid Dynamics Simulation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Like the heat sink effect, warm blood flows into locally cooled tissues and raises temperature during cryoablation so it becomes difficult to cover the entire region of diseased tissues with the ice ball. Computational studies of the effects of arterial bifurcation (branching) on the temperature distribution during cryosurgery have shown that the convective heat transfer from bifurcated vessels can limit ice ball formation, cause irregular ice ball shape near the arterial bifurcation and prevent the blood vessels from being frozen 15 . Hence, areas of tissue that have high vascularity may see less benefit from cryoablation, although artery walls may benefit from lower susceptibility to ice-induced damage.…”
Section: Cryoablation Cancer Therapy and Action Mechanismmentioning
confidence: 99%